Pengembangan Sistem Informasi Konstituen Menggunakan Rapid Application Development - Lalu Mutawalli; Mohammad Taufan Asri Zaen; Khairul Imtihan (JURIKOM (Jurnal Riset Komputer), 2022)
Constituent data collection for each member of Dewan Perwakilan Rakyat Daerah (DPRD) becomes a necessity. By conducting data collection of DPRD constituents will be easier to design the main points of the DPRD constituents who are aspirations from the constituents. Better constituent data processing is very necessary considering today in the absence of a system specifically for processing constituent data. The study conducted with members of the East Lombok Regency DPRD wants the development of constituent information systems to be developed quickly. The problem in this study is in a short period, therefore this study proposed Rapid Application Development (RAD) as a methodology in modeling the problem of developing information systems. RAD is a life cycle providing a way to design and develop information systems much faster with results that have high-value quality. Based on the test results on the system, testing is carried out by considering the three aspects, the first is the quality of this system aims to test the interface (interface), namely ease of use, response time, and language. Based on the results of testing the quality of the system obtained a score of 87% of the 13 respondents. Both assessments on the quality of information, this assessment aims to measure the accuracy of the information, information. Based on the results of the test, the assessment score was 83% while the third related to the quality of the Constituent Information System Service received as much as 85%. So the average results of the assessment of the entire type of testing obtained a score of 85% that the information system developed has been by the user's requirements.